Photography - Butterfield, Moira, 1961-; Peach, Susan (London : Usborne ; Tulsa, Okla. : EDC, 1987)
Provides advice for taking all kinds of successful photographs.
6.3
5-8
Keywords: Photography -- Juvenile literature; Photography; Photography